Optimization of glucose production from sugarcane bagasse using response surface methodology (rsm) - Zaidatul Akmal, Mohd Mustapha (2010)
Glucose benefits much for industry, medical field and researches. Old method in producing glucose involved chemical process throughout the procedures. This method is not environmental friendly. Research showed that the production of glucose was successfully obtained from plant biomass. The purpose of this study was to optimize the glucose production from sugarcane bagasse using Response Surface Methodology (RSM). Bagasse is the sugarcane residue after juice extraction. The parameters used in this research were temperature, substrate (cellulose from bagasse) dose and enzyme (cellulase from Aspergillus niger) dose. The bagasse was treated with alkali before enzymatic hydrolysis procedure took place for glucose production. Screening process conducted in this study was to determine the best range of parameters involved and this range would be used for the optimization using RSM. Seventeen experiments have been arranged by RSM for analysis. RSM predicted the best conditions of parameters were 45°C of temperature, 1.3 g of substrate dose and 0.8 g of enzyme dose with the glucose production was 5.8672 g/L. The validation of experiment showed that glucose production was 5.725 g/L compared to predicted value, 5.8672 g/L. Before optimization, the production of glucose was 1.010 g/L with conditions 45°C of temperature, 2.0 g of substrate dose and 1.0 g of enzyme dose. The percentage of increment was 82.36%. From these observation and analysis, it can be concluded that the objective of this research to optimize the glucose production from sugarcane bagasse using Response Surface Methodology (RSM) was successfully conducted.